Protonation-Induced Planarization and Aromaticity Enhancement in Diazahelicenes: A Route to Stronger Bases - Mathew, Manjesh; Puchta, Ralph; Thomas, Renjith (Journal of Physical Chemistry A, 2026)
In this study, we investigated the exceptional basicity of diazahelicenes through a comprehensive computational analysis using DFT calculations. Eighteen diazahelicene compounds were examined and compared with 1,8-bis(dimethylamino)naphthalene (DMAN), revealing that most exhibit stronger basicity than DMAN, qualifying them as proton sponges. The study employed the M06-2X functional with the def2tzvp basis set to analyze proton affinity, gas-phase basicity (GB), and structural changes upon protonation. We found that the basicity is significantly influenced by the interplanar angle, hydrogen bonding, conjugation, and aromaticity of the compounds. Most compounds demonstrated a decrease in interplanar angle upon protonation, with compounds containing nitrogen atoms in close proximity showing frustrated base behavior. Aromaticity analysis using HOMA (Harmonic Oscillator Model of Aromaticity) and Nucleus-independent Chemical Shift indices indicated enhanced electron delocalization after protonation. Further insights into electronic structure and bonding were obtained through AIM (atomic in molecules), MEP (molecule in electrostatic potential), NBO (Natural Bonding Orbital), ELF (electron localization function), and LOL (Localized Orbital Locator) analyses, providing a comprehensive understanding of the factors contributing to the exceptional basicity of these compounds.
CRIS-Team Scopus Importer:2026-01-23